8 Guide steps for setting up a Climate-Smart Village (CSV) - Sebastian, Leocadio S.; Gonsalves, Julian Francis; Bernardo, Eisen Bernard (2019)
The brief elaborates the 8 steps in setting up a Climate-Smart Village (CSV). The eight steps are: determining the purpose and scope of CSV; identifying the climate risk in the target area/s; locating the CSV in a small landscape; consulting the stakeholders; evaluating the CSA options; developing portfolio; scaling-up; and monitoring and evaluating uptake and outcome.